Developing academics' assessment practices in open, distance and e-learning: an institutional change agenda. (3rd May 2016) - Evans, Jessica; Jordan, Sally; Wolfenden, Freda
Abstract: Universities across the globe are attempting to change assessment practice to address challenges in student engagement and achievement. Integral to this objective are strategies to develop academics' assessment practice. These frequently focus on attendance at formal Continuous Professional Development events and/or implementation of institutional blueprints. This editorial article uses a case study from the Open University (UK) to explore an alternative 'communities of practice' approach to the improvement of assessment arguing that academics' professional expertise is best deepened through participation in authentic activities of teaching and scholarship. The discussion identifies what is involved in such an approach including the role of an enabling principles-based framework, the constraints on implementation and the implications for HE leaders.